2014
DOI: 10.1038/srep06968
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced metallization of dense (H2S)2H2 with high-Tc superconductivity

Abstract: The high pressure structures, metallization, and superconductivity of recently synthesized H2-containing compounds (H2S)2H2 are elucidated by ab initio calculations. The ordered crystal structure with P1 symmetry is determined, supported by the good agreement between theoretical and experimental X-ray diffraction data, equation of states, and Raman spectra. The Cccm structure is favorable with partial hydrogen bond symmetrization above 37 GPa. Upon further compression, H2 molecules disappear and two intriguing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

113
928
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 1,002 publications
(1,089 citation statements)
references
References 49 publications
113
928
5
1
Order By: Relevance
“…(ii) Polyhydrides with nontraditional stoichiometries, in some cases containing an H 2 sublattice, should be stable. (iii) These hydrogen-dense systems may become metallic at much lower pressure than expected for metallic hydrogen and could have a high-temperature superconductivity (8,9). These theoretical results have impelled an active experimental search (e.g., refs.…”
mentioning
confidence: 99%
“…(ii) Polyhydrides with nontraditional stoichiometries, in some cases containing an H 2 sublattice, should be stable. (iii) These hydrogen-dense systems may become metallic at much lower pressure than expected for metallic hydrogen and could have a high-temperature superconductivity (8,9). These theoretical results have impelled an active experimental search (e.g., refs.…”
mentioning
confidence: 99%
“…The ideas of Ashcroft have been recently confirmed by the experiments of Drozdov et al [6] and a series of theoretical papers [7][8][9][10][11][12][13][14] that confirm hydrogen-based hightemperature superconductivity is realized in the sulfur *Corresponding Author: D. A. Papaconstantopoulos: Department of Computational and Data Sciences, George Mason University, Fairfax, Virginia 22030, USA, E-mail: dpapacon@gmu.edu compound H 3 S under 200 GPa pressure. Reference [8] presents a comprehensive set of calculations for H 3 S using the GGM theory.…”
Section: Introductionmentioning
confidence: 89%
“…The number of papers published on the theory and modelling of high T c superconductivity in hydrogen sulfide has increased rapidly since 2014, see for example Refs. [15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent to the work of Li et al, 15 Duan et al 16 reported a DFT study of (H 2 S) 2 H 2 at high pressures. They investigated several H/S structures including H 3 S-R3m which is stable at lower pressures and was estimated to have a T c of ∼160 K at 130 GPa, and the higher pressure H 3 S-Im3m phase that was estimated to have a T c of around 200 K at 200 GPa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation